Enhancing Environmental Sustainability of Airports in Indonesia through Green Technology: Strategies for Pollution Reduction and Climate Change Adaptation - Rohimah, Siti Mimah; Effendi, Yunus (Universitas Al Azhar Indonesia, 2024)
Climate change and pollution generated by the transportation sector, particularly airports, present major challenges in achieving environmental sustainability. This article discusses the application of green technology at Indonesian airports as a strategy to reduce pollution and adapt to climate change. The main focus of this study is to identify various environmentally friendly technologies that can be implemented at airports, such as the use of renewable energy, efficient waste management, and energy-efficient building design. Additionally, this article explores the policies and challenges faced in the implementation of green technology at Indonesian airports. The findings show that implementing green technology can significantly reduce airport carbon footprints, improve operational efficiency, and reduce negative environmental impacts. Therefore, the development and application of green technology at Indonesian airports is a crucial step in supporting climate change mitigation and achieving environmental sustainability in the air transportation sector.Keywords – Environmental Sustainability, Indonesian Airports, Green Technology, Pollution Reduction, Climate Change Adaptation, Renewable Energy, Waste Management, Energy Efficiency